Evidence of Ostrea lurida (Carpenter 1864) population structure in Puget Sound, WA - Heare, J. Emerson; Blake, Brady; Davis, Jonathan P.; Vadopalas, Brent; Roberts, Steven B. (PeerJ PrePrints, 2015)
Where restoration efforts occur, such as with Ostrea lurida in Puget Sound, Washington, it is important to consider genetic population structure. Traits that hold adaptive advantage such as reproductive timing and stress resilience may differ at local scales. Using three established populations of O.lurida within Puget Sound Washington, we performed a reciprocal transplant experiment and monitored survival, growth, reproduction. We found that performance differed for each population at each of these three metrics. O.lurida from a relatively harsh home site environment with low primary production and high dynamic habitats exhibited generally greater survival at all sites, whereas those from a relatively lush home site environment with high primary production and lower habitat dynamics exhibited generally greater reproductive activity at all sites. Populations from sites with shorter growing seasons exhibited greater growth in sites with longer growing periods, suggesting a countergradient adaptation may have occurred in these populations.
Keywords: Ostrea lurida; Restoration; Growth; Mortality; Reproduction; Population Structure